JHEA, Volume 18, n° 1, 2020 - Full Issue - Journal System (Journal of Higher Education in Africa, 2021)
Special Issue on The Politics of Knowledge Production in Africa (With selected papers from the 15th CODESRIA General Assembly) Contents Academic (Im)mobility: Ecology of Ethnographic Research and Knowledge Production on Africans in China Kudus Oluwatoyin Adebayo..........................................................................1 What Should Globalization Mean for African Humanities and Why? Lawrence Ogbo Ugwuanyi..........................................................................23 Sociology of Knowledge in the Era of Academic Dependency in Africa: Issues and Prospects Oludele Albert Ajani..................................................................................39 Situating African Indigenous Ideas within Conventional Learning as an Impetus for Knowledge Construction in Africa Babatunde Joshua Omotosho.................................................................53 Skills or Credentials? Comparing the Perspectives of Degree- and Non-degree-holding Ghanaian Graduates on the Value of Higher Education Nana Akua Anyidoho............................................................................67 Globalisation, Decoloniality and the Question of Knowledge Production in Africa: A Critical Discourse Olugbemiga Samuel Afolabi..............................................................93 Propos sur un Bandoeng épistémique: l’Afrique, le Sud Global et la production du savoir à l’ère de la mondialisation Germain Ngoie Tshibambe................................................................111